EVALUASI PARKIR KENDARAAN (ON THE STREET PARKING) PADA JALAN DR. RADJIMAN KOTA SURAKARTA - Maulana Wakhid Riffani; Teguh Yuono; Rasyiid Lathiif Amhudo; Ade Sandhy Atmaja; Tuan Noor Rafidah Binti Tuan Hassan (Journal of Civil Engineering and Infrastructure Technology, 2026)
The development of economic activities and the increasing number of motor vehicles in Surakarta City have led to a high demand for parking space, particularly in commercial center areas. One of the emerging problems is the use of road shoulders as parking areas (on-street parking), which has the potential to reduce road performance. Dr. Radjiman Street in Surakarta City is one of the road segments with high parking activity due to its location in a commercial district, frequently causing traffic congestion. This study aims to identify the existing parking conditions, analyze the characteristics of on-street parking, and determine the most appropriate solutions to meet parking demand on Dr. Radjiman Street, Surakarta City. The research method employed was a field survey, with primary data collection including vehicle entry and exit data, parking duration, parking volume, parking accumulation, parking index, parking turnover, and road geometric data. The survey was conducted on Saturdays and Sundays to represent days with high parking activity. The results indicate that the existing parking capacity is insufficient to accommodate four-wheeled vehicles, as reflected by parking index values exceeding 100% during certain hours. This condition leads to excessive use of the roadway, reducing the effective road width and disrupting traffic flow. Based on the analysis, a reorganization of parking patterns with appropriate parking angles, along with the optimization of off-street parking facilities, is required as a solution to reduce on-street parking. It is expected that the findings of this study can serve as a reference for relevant stakeholders in managing and organizing parking facilities to improve traffic performance on Dr. Radjiman Street, Surakarta City.